(untitled) (Ágora Journal, 2021)
This paper aims to problematize and discuss the ways in which the poet Augusto dos Anjos (1884-1914) represented tuberculosis in the verses of one of his poems, entitled Os Doentes, included in the first edition of his only book, Eu, published in the city of Rio de Janeiro in 1912. Through our analysis, we try to understand the historical meanings that his verses express as they elaborate such literary representations.